Qualitative Research for Physical Culture - Markula, P. author. aut Link
XIII, 252 p.
Keywords: This book provides a guide to qualitative research methods in the multidisciplinary field of physical culture. Developing an approach based on the '7 Ps' of research, this text navigates a pathway through the research process that will be invaluable as a teaching tool and to experienced and inexperienced researchers alike.